Potencial maderable y valorización económica de las especies forestales comerciales del bosque siempreverde ubicado en el recinto Valle del Sade Cantón Quinindé, Provincia de Esmeraldas - Carbo Jiménez, Rony Yael (2021)
This research analyzes the timber potential and economic valuation of commercial forest species that was developed in the evergreen forest area of Mr. Rodolfo Iván Villafuerte Piedrahita, which has a total area of 31.6 ha, the entire area was inventoried. The objective was to determine the timber potential and valuation of commercial forest species in this forest. The Hypothetical-Deductive method was used, using a descriptive, explanatory and correlated analysis, which allows the observation of the phenomenon to be studied. A total of 444 individuals were recorded, 28 tree species, corresponding to 18 botanical families, the most representative species was Hyeronima alchorneoides with 101, followed by Brosimum utile with 46 and those with the least number were Brosimum spp. and Sloanea grandiflora, all individuals were classified in 10 diameter classes, in which there are 73 individuals with a diameter between 46 and 55 cm and 9 in the classes between 116 and 125 cm. The timber potential per standing diameter class was 2886,064 m3 and the volume to be mobilized was 1443,032 m3. The economic value of the forest was $105,468 in total profitability, with a benefit-cost ratio of $1.78, which shows that the profitability of these harvested species is currently based on their market value, so their commercialization is regular. Based on the results obtained, it is proven that there is a high timber potential of the tree species in the evergreen forest, so its timber potential is considerably high in relation to the study area. Keywords: Forest, harvesting, profitability, species